Pulsatile Powell-Eyring Nanofluid Flow in a Channel with Inclined Magnetic Field and Chemical Reaction - SRINIVAS, Suripeddi; CHALLA, Kalyan Kumar; BADETI, Satyanarayana; KUMAR, P. Bharath (Engineering Transactions, 2023)
The current article addresses the impacts of the pulsatile flow of Powell-Eyring nanofluid using Buongiorno’s model in a horizontal channel. It also describes the combined impacts of thermophoresis and Brownian motion. Blood is an example of a Powell-Eyring fluid. The Runge-Kutta (R-K) 4th-order method, along with the shooting technique, is used to determine solutions for velocity, temperature, and concentration. The impacts of different parameters, including an inclined magnetic field, chemical reaction, Lewis number, and heat source or sink parameter, are illustrated graphically. The mass flux distribution decreases due to an increase in the values of the Powell-Eyring fluid parameter.